Mild Anemia and Pregnancy Outcome in a Swiss Collective. (13th November 2014) - Bencaiova, Gabriela; Breymann, Christian
Abstract : Background . Over half of all women in the world experience anemia during their pregnancy. Our aim was to investigate the relation between hemoglobin and iron status examined in second trimester and pregnancy outcome. Methods . In a prospective longitudinal study, 382 pregnant women were included. Blood samples were examined for hematological status and serum ferritin between 16 and 20 weeks and for hemoglobin before delivery. The adverse maternal and perinatal outcomes were determined. Regression analysis was performed to establish if anemia and low serum ferritin are risk factors for pregnancy complications. Results . There was no increase of complications in women with mild anemia and in women with depleted iron stores. The finding showed that mild iron deficiency anemia and depleted iron stores are not risk factors for adverse outcomes in iron supplemented women. Conclusions . Mild anemia and depleted iron stores detected early in pregnancy were not associated with adverse maternal and perinatal outcomes in iron supplemented women.